2008
DOI: 10.1097/01.jcn.0000317449.87649.8e
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice to Assist Women in Hospital Settings to Quit Smoking and Reduce Cardiovascular Disease Risk

Abstract: Smoking and obesity are widely recognized cardiovascular risk factors for significant morbidity and mortality in women. Although women still smoke less than men do, smoking among women is on the increase, especially in younger women and teenagers. Reduction of cardiovascular risk through smoking cessation while maintaining weight is a major goal of intervention. The purpose of this article is to discuss best care practices for women with tobacco addiction using a 3-point integration of clinical expertise, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
5
0
4
Order By: Relevance
“…Out of the total studies conducted in general health services, three were developed in cervical cancer prevention services, 10 , 11 , 23 two in specialized health services in women’s health, 18 , 21 and one in services that aim to decrease the risk of cardiovascular diseases. 8 In cervical cancer prevention services, most women were young average-aged, were highly level educated, were married, and were employed; two of the three studies were performed in Italy. 10 , 11 In the specialized health services in women’s health, women were young-aged and highly level educated; however, in the services aimed at decreasing the risk of cardiovascular diseases, most women were middle-aged, were highly level educated and were employed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the total studies conducted in general health services, three were developed in cervical cancer prevention services, 10 , 11 , 23 two in specialized health services in women’s health, 18 , 21 and one in services that aim to decrease the risk of cardiovascular diseases. 8 In cervical cancer prevention services, most women were young average-aged, were highly level educated, were married, and were employed; two of the three studies were performed in Italy. 10 , 11 In the specialized health services in women’s health, women were young-aged and highly level educated; however, in the services aimed at decreasing the risk of cardiovascular diseases, most women were middle-aged, were highly level educated and were employed.…”
Section: Resultsmentioning
confidence: 99%
“…Dos estudos realizados em serviços de saúde geral, três foram desenvolvidos em serviços de prevenção de câncer cervical, 10 , 11 , 23 dois em serviços de saúde especializados em saúde da mulher, 18 , 21 e um em serviço que visa a diminuir o risco de doenças cardiovasculares. 8 Nos serviços de prevenção de câncer cervical a maioria das mulheres apresentavam faixa etária média jovem e alto nível educacional, exerciam atividade remunerada e eram casadas; dois dos três estudos foram realizados na Itália. 10 , 11 Nos serviços de saúde especializados em saúde da mulher, as mulheres situavam-se na faixa etária jovem e tinham um alto nível escolar; já nos serviços que visavam a diminuir o risco de doenças cardiovasculares, a maioria das mulheres estavam na meia idade, exerciam atividade remunerada e tinham alto nível educacional.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Two studies of hospitalized clients that used content similar to the one in this study found that self-instructional diary or telephone delivery of content was not very interactive or interesting and required appointments that clients had difficulty keeping (Buchanan, El-Banna, Siedlik, White, & Wood, 2004;Buchanan & Likness, 2008). An alternative method of delivery for clients who have difficulty keeping structured appointments is the use of computer, cellular phone, or PDA technology (Fiore et al, 2008;Kwon & Chidambaram, 2000).…”
Section: Sustaining Smoking Cessation After Dischargementioning
confidence: 86%
“…One interesting approach is the FRIENDS-SIM (Follow-up Relationships Intended to End Smoking-Self-Instruction Manual) intervention, which uses a manual that supports patients during cravings, a key risk for smoking relapse [46]. The FRIENDS-SIM intervention found a need to further strengthen education and skills acquisition for partner support [47]. The use of technology such as a personal digital assistant could be an alternative to the manual that would allow easier use and portability [48].…”
Section: Smoking Cessationmentioning
confidence: 98%